Assessment of the gonadotrophin–gonadal axis in androgen insensitivity syndrome. Issue 4 (1st April 1999) - Ahmed, S F; Cheng, A; Hughes, I A
Abstract : OBJECTIVE: To study the value of measuring serum luteinising hormone (LH), follicle stimulating hormone (FSH), testosterone, and dihydrotestosterone (DHT) in androgen insensitivity syndrome (AIS). DESIGN: Retrospective study of patients on a nationwide register of AIS. PATIENTS: Sixty one cases of AIS with androgen receptor (AR) dysfunction (abnormalities of the AR gene and/or abnormal AR binding) were divided into three age groups: infants, < 1 year old; children, 1–13 years old; and postpubertal, > 13 years old. MEASUREMENTS: Age, dose of human chorionic gonadotrophin (hCG) stimulation, pre-hCG and post-hCG serum testosterone values, serum DHT values, and serum LH and FSH values before and after LH releasing hormone (LHRH) stimulation. RESULTS: In 23 of 30 infants testosterone was within age related reference ranges; six were above this range. The median testosterone rise following variable dosage of hCG was 9.5 times the basal value. The increment was not related to the hCG dose, age, or basal concentration of testosterone. The median basal and stimulated testosterone:DHT ratios were 2.5 and 6.1, respectively. The median increment in DHT was 2.2-fold. Seventeen of 18 FSH and 11 of 19 LH measurements were within age related ranges in infants; in seven patients LH values were above the range. LHRH stimulation performed in 39 patients showed an exaggerated LH in all age groups. The FSH response was not exaggerated in children. CONCLUSION: Although a positive hCG test excludes biosynthetic defects of testosterone, an inadequate response does not exclude AIS. Basal LH and testosterone may not be raised during early infancy. An LHRH stimulation test might be useful for evaluating cases of suspected AIS presenting in mid-childhood.